A single lysergyl peptide synthetase assembles lysergic acid amides in Aspergillus species - Samantha J. Fabian; Abigail M. Jones; Jessica L. Fuss; Daniel G. Panaccione (PLoS ONE, 2026)
The agriculturally and pharmaceutically important lysergic acid amides ergonovine and lysergic acid α-hydroxyethylamide (LAH) are synthesized from a lysergyl-alanine precursor. In ergot-alkaloid producing fungi of the family Clavicipitaceae, lysergyl-alanine is assembled and then reduced to ergonovine by a complex of two monomodular nonribosomal peptide synthetases: lysergyl peptide synthetase 2 (Lps2) and Lps3. LAH is the major ergot alkaloid product of these fungi when the Lps2/Lps3 complex interacts with the Bayer-Villiger monooxygenase encoded by easO . An α/β hydrolase fold protein encoded by easP increases LAH accumulation but is not essential for LAH biosynthesis. Lps2 and Lps3 do not occur in the several species of Aspergillus (including A. leporis ) that produce LAH and ergonovine. Instead, ergot alkaloid synthesis clusters of these Aspergillus species encode a novel two-module Lps gene, lpsD . We hypothesized the product of lpsD was functionally equivalent to the two separately encoded, monomodular enzymes of the Clavicipitaceae and tested this hypothesis by introducing lpsD of A. leporis into a strain of Aspergillus fumigatus that had been modified previously to accumulate lysergic acid as substrate. Introduction of lpsD resulted in accumulation of ergonovine as evidenced by high-performance liquid chromatography and liquid chromatography-mass spectrometry. The addition of the A. leporis allele of easO into the lpsD -transformed A. fumigatus strain led to accumulation of LAH. Introduction of a construct containing easP as well as easO into the lpsD -transformed A. fumigatus strain resulted in higher concentrations of LAH than in strains containing only lpsD and easO , consistent with previous studies in the Clavicipitaceae. The data support the hypothesis that ergot alkaloid-producing Aspergillus species independently evolved a single enzyme that serves the purpose of the two monomodular peptide synthetases of the Clavicipitaceae.